2019
DOI: 10.1186/s13722-019-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ satisfaction with providing buprenorphine treatment

Abstract: Background Buprenorphine is a critically important treatment for addressing the opioid epidemic, but there are virtually no studies of physicians’ job satisfaction with providing buprenorphine. Physicians’ job satisfaction has been linked to burnout and turnover as well as patients’ adherence to treatment recommendations, so it is important to understand how physicians’ satisfaction with providing buprenorphine treatment compares to their overall job satisfaction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The literature is sparse regarding job satisfaction, perceived support, and job-related self-esteem of providers delivering MOUD, and what is available is limited to primary care prescribers [ 30 , 33 , 38 , 39 ]. Consistent with a prior study, our respondents from multiple disciplines reported high satisfaction with treating patients with OUD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is sparse regarding job satisfaction, perceived support, and job-related self-esteem of providers delivering MOUD, and what is available is limited to primary care prescribers [ 30 , 33 , 38 , 39 ]. Consistent with a prior study, our respondents from multiple disciplines reported high satisfaction with treating patients with OUD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature is sparse regarding job satisfaction, perceived support, and job-related self-esteem of providers delivering MOUD, and what is available is limited to primary care prescribers [ 30 , 33 , 38 , 39 ]. Consistent with a prior study, our respondents from multiple disciplines reported high satisfaction with treating patients with OUD [ 38 ]. Further, providers reported positive views of their effectiveness and comfort working with patients who use opioids, as well as their knowledge of opioid use and related consequences, and ability to access support from colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published by Becker and Fiellin in 2005 [ 17 ] noted a gap in the literature regarding prescriber satisfaction with delivering buprenorphine treatment. Since that review, there have been two publications regarding prescriber satisfaction, one a qualitative study of rural prescribers [ 18 ] and the other a survey of a small sample of physicians in three states [ 19 ]. Andrilla and colleagues found that rural prescribers described their buprenorphine practice as rewarding and meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…Andrilla and colleagues found that rural prescribers described their buprenorphine practice as rewarding and meaningful. However, a survey of waivered physicians indicated that prescribers rated their buprenorphine work as significantly less personally rewarding when compared to their general medical practice [ 19 ]. To date, there have been no studies of prescriber satisfaction with delivering XR-naltrexone as a treatment for OUD.…”
Section: Introductionmentioning
confidence: 99%
“…Knudsen et al report findings of physician satisfaction with providing buprenorphine treatment across three states [1]. While this report of baseline data from a larger study evaluating different approaches to implementing buprenorphine treatment for opioid use disorder (OUD) into ambulatory settings [2] is small in sample size and reach, it raises an important issue that should be addressed for all projects attempting to expand the number of providers offering buprenorphine: provider satisfaction.…”
mentioning
confidence: 99%